Winter Growth of Carps under Different Semi-Intensive Culture Conditions - Nadia Nazish* and Abdul Mateen (Pakistan Veterinary Journal, 2011)
The experiment was planned to observe the influence of different semi intensive culture conditions i.e. organic and inorganic fertilizer with rice polish on the growth of carps during winter season. Two earthen ponds were selected and each pond was stocked with Silver carp (Hypophthalmichthys molitrix), Rohu (Labeo rohita) and Mori (Cirrhinus mrigala) at the ratio of 1:2:1 respectively with a total number of 44 fishes. Pond 1 was treated with poultry dropping and urea while pond 2 was treated with poultry dropping, urea and rice polish. The ponds were treated with at the rate of 0.2 g N/100g of wet body weight of fish. Fertilizers were added on weekly basis while rice polish was added daily. Total net fish production of pond 1 and pond 2 was remained 797.3 and 1033.0 kg/ha/year. The pond treated with fertilizer and artificial feed (rice polish) showed 3.6% more fish production than the pond treated only with fertilizer. The physico-chemical parameters were measured on weekly basis. Temperature, light penetration, pH and planktonic biomass showed non-significant difference in both ponds. Pond 2 which was treated with poultry dropping, urea and rice polish showed 1.26 times greater fish growth than pond 1 which was treated with poultry dropping and urea.